Numerical studies of riblets in duct flow - Chua, Yu Zheng (2019)
The present study investigates the drag reduction capabilities of semi-circular riblets lined along the bottom surface of a square duct. The use of semi-circular riblets is inspired from studies on wavy surfaces in channels to emulate skin folds on dolphins which were postulated to have drag reduction capabilities. In the present study, the k- SST model is used to simulate the turbulent flow and the riblets are placed in three different configurations (normal to stream wise flow, angled at 80 degrees to stream wise flow and symmetrically). For each configuration, the amplitudes of the riblets are fixed at 0.5mm while the distance between each riblet is varied from 15mm to 25mm at 5mm intervals. As such, a total of 9 samples and 1 control are tested in the present study. The Reynolds number based on bulk velocity and hydraulic diameter is varied from 7994 to 20786. The results obtained from the numerical studies revealed that the riblets have friction drag reducing capabilities. When the three different configurations are compared, it was found that the “Normal” configuration had the best friction drag reducing capabilities. It was also observed that each configuration affected the wall shear stress distribution on the bottom surface differently. In the case of the “Normal‟ configuration, the wall shear stress are flushed towards the sides. For the “Angled” configuration, the wall shear stresses are skewed towards the side where the fluid first comes into contact with the riblet. Lastly, the “Symmetric” configuration revealed higher levels of wall shear stresses towards the centre. Even though the riblets achieved friction drag reductions, it was found that the total drag across the square duct increases due to the addition of the riblets. Upon analysis of the stream wise flow, it was found that flow separations occurred across each riblet which led to increased pressure drag. This increase in pressure drag outweighs the reduction in friction drag, hence explaining the increase in total drag. In terms of pressure drag, the “Symmetric” configuration resulted in the least pressure drag increment compared to the other two configurations. From the present study, it was concluded that semi-circular riblets offer the benefits of friction drag reduction at the expense of increased pressure drag and hence might not be a good choice of total drag reduction method.